The Role of Citizen Participation and the Use of Social Media Platforms in the Participatory Budgeting Process. Issue 1 (2nd January 2017) - Gordon, Victoria; Osgood, Jeffery L.; Boden, Daniel
ABSTRACT: In the United States participatory budgeting (PB) is a relatively new and innovative approach to municipal budgeting that has implications for improving the role of citizen participation in the budgetary process. The research is based on personal interviews with local community leaders involved in the PB process in the 49th Ward of Chicago, Illinois; the 6th Ward of St. Louis, Missouri; and the City of Boston, Massachusetts. Highlights are provided of the specific experiences and perceptions of these community leaders with a particular emphasis on the use of social media platforms in engaging citizens in the PB process. This article concludes with recommendations for creating a PB infrastructure, for increasing citizen participation in the PB process, and for assessing and increasing the impact of PB in cities within the United States.